Content preservation analysis of Semarang City tourism website - Pramudibyanto, Hascaryo (Daluang: Journal of Library and Information Science, 2023)
Background. Semarang City tourism site is a means to market the tourism business industry has not been managed properly. The niche on the tourism website has not shown a complete description of the actual conditions of a digital collection preservation effort. This study aims to analyze content preservation on tourism websites in Semarang City. The purpose of this research is to describe the excellence of Semarang City tourism website when filled with complete and attractive content. Methodology. This study on preservation analysis of tourism websites uses descriptive qualitative methods by conducting media content analysis on the tourism website http://pariwisata.semarangkota.go.id/ as tourism information navigation. The core of the problem studied is the lack of relevance of Semarang City's development plan as a smart city with the readiness of tourism information. Results and discussion. The results of the content analysis of the preservation of the site found that the content of the site has not fully conveyed actual and interesting ideas, ideas, or information. Conclusions. Preservation efforts have been done well, but the quality of this niche on the site needs to be improved. This site is still undergoing an application maintenance process so there is a delay in updating the site content. Suggestions for site improvement include providing opportunities for the community to send coverage products about tourism activities through an editing process to harmonize the content with other aspects of beauty. Visitors expect an honest statement from the site manager to apologize that this site is undergoing application maintenance or preservation so that visitors can figure out the actual situations